PERANCANGAN VIDEO COMPANY PROFILE PT. PERTAMINA DENGAN PENDEKATAN PSIKOLOGI - Kholifah Raihanun Navira; Tata Sutabri (Jurnal Salome : Multidisipliner Keilmuan, 2023)
This study aims to design Video Company Profile of PT. Pertamina (Persero) using a psychological approach. This research is a descriptive research using secondary data. Secondary data in this study was obtained through library methods, internetm and also documenting relevant and needed data and information about PT. Pertamina (Persero). The design stages that must be passed are pre-production, production, and post-production. The results showed that researchers have elaborated on the psychological aspects in designing this video in accordance with the approach taken, where the psychological aspects in question are aspects of object selection and color gradation selection. The recommended suggestion is that this design not only reaches the tentative stage but also to the execution stage which displays the final results of the Company Profile Video design itself.